Voting Islamist or voting secular? An empirical analysis of voting outcomes in Arab Spring Egypt - May Elsayyad; Shima'a Hanafy (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
This paper empirically studies the voting outcomes of Egypt's first parliamentary elections after the Arab Spring. In light of the strong Islamist success in the polls, we explore the main determinants of Islamist vs. secular voting. We identify three dimensions that affect voting outcomes at the constituency level: the socio-economic profile, the economic structure and the electoral institutional framework. Our results show that education is negatively associated with Islamist voting. Interestingly, we find significant evidence which suggests that higher poverty levels are associated with a lower vote share for Islamist parties. Later voting stages in the sequential voting setup do not exhibit a bandwagon effect.
Keywords: D72; D78; O53; P26; Z12; Z13; 330; Voting Outcomes; Arab Spring; Political Islam; Sequential Voting